Physicochemical, Functional Properties And Mycotoxin Occurrence Of Ghanaian Tigernuts (Cyperus Esculentus L.) - Battuta-Dawlah (University of Ghana, 2022)
In Ghana, tigernut (Cyperus esculentus L.) is grossly underutilized in food applications and is mostly consumed raw as a snack. However, the soil and climate conditions of the country are conducive for cultivation of the crop on a large scale for applications in food for local consumption, industrialisation and for the export market. Food applications of tigernut and its derivatives and their possible inclusion as ingredient in the Ghanaian diet would require knowledge on its handling quality and functional properties. The aim of this study was to characterise Ghanaian tigernut as an ingredient for possible food applications. The study design consisted of two parts: (a) a cross-sectional survey of different categories of stakeholders using pre-tested semi-structured questionnaires (b) followed by laboratory designed experiments to study the quality, physicochemical and functional properties of tigernut as a function of tigernut variety and process conditions. For the surveys, a total of 1277 stakeholders in the value chain, comprising of 711 consumers and 487 traders (wholesalers/retailers) in Greater Accra region and 79 tigernut farmers in the Western and Eastern regions of Ghana, were interviewed using semi-structured researcher-administered questionnaires. The questionnaires sought to gain information on respondents’ level of knowledge on mycotoxins, as well as ascertain if measures were in place to mitigate the risk of fungal colonisation of the crop along the supply chain. Additionally, tigernuts collected at various points along the supply chain (farm, wholesale and retail) were analysed for their mycotoxin (aflatoxins and ochratoxin A) levels using reverse phase High-Performance Liquid Chromatography (HPLC), to determine the hot spots of mycotoxin contamination along the value chain. The second part of the study investigated the physical characteristics of tigernut tubers as well as the functional properties of tigernut flour with the aim of determining its suitability in food applications. Additionally, the shelf life of the tigernut flour was determined by accelerated shelf life testing using the Arrhenius model. Fresh tigernut milk is usually University of Ghana http://ugspace.ug.edu.gh iii characterised by the sedimentation of starch which influences its flow behaviour as well as the physical stability. Furthermore, heat treatment of the milk leads to gelatinisation of the starches, which also affects the same properties. Consequently, the effects of heat (by roasting tigernuts) and adding α- amylase to the tigernut milk on the physicochemical and functional properties of tiger nut milk were studied. Tigernut oil was extracted and the phenolic and functional properties were determined as well as the effect of heat on these properties. The macro nutritional composition of tigernut tuber, flour, oil and milk were also investigated. The results of the surveys showed that tigernut farmers and consumers had appreciable knowledge in and displayed better attitude towards the prevention of mycotoxin contamination than the tigernut traders (wholesalers/retailers). The educational level of all stakeholders influenced their attitude and knowledge towards the prevention of mycotoxin contamination. Almost all consumers were willing to try new tigernut products such as the flour, oil and milk and would like to see more of these products on the Ghanaian market. The number of samples and the levels of mycotoxins (Ochratoxin A and aflatoxins) increased as the value chain progressed, with retail samples containing all the mycotoxins analysed. Total mycotoxins ranged from 0-27 µg/kg at the farm stage to 0-52 µg/kg at the wholesale stage and finally to 7.9 to 1115.48 µg/kg at the retail stage. These highlight post-harvest stage of the value chain as the focal point for mycotoxin prevention programs, although mycotoxin prevention can be agreed as a cumulative process. Both black and yellowish-brown tigernut flours contained relatively high and comparable amounts of sucrose, glucose and fructose. The relatively high resistant starch content of the tigernut flour makes the flour ideal for diabetics and weight watchers. The yellowish-brown variety had higher total starch content, higher water-retaining ability and viscosity at heating and holding cycles as compared to the black variety. Titratable acidity was found to be the crucial determinant of spoilage in tigernut flour and higher temperature was observed to increase the oxidation of the tigernut flour. This may imply that tigernut flour should be stored below room temperature. Heat and the addition of α- amylase increased the total solids, brix and titratable acidity but caused a decrease in the pH of the tigernut milk. Addition of 0.2% of α- amylase to roasted tigernut milk improved its emulsion stability. Heat and addition of α- amylase caused the tigernut milk to become darker in colour. The flow behaviour of the tigernut milk exhibited shear thinning (pseudoplastic) fluid properties. This implies that commercial production of milk from tigernut must control parameters such as speed of machines during processing as well as concentrations of food additives such as α-amylase. Chemical qualities such as iodine value, peroxide value, ester value, saponification value, free fatty acids and acid value of oil extracted from tigernut tubers, all increased at higher temperatures whilst antioxidant activity and phenolic content decreased. The functional properties of tigernut oil suggested that the oil is good for frying at lower temperatures and for shorter periods. The carbohydrate component of the tigernut tuber was mainly made up of starch and dietary fibre (resistant starches) which reduced in the milk and oil. Crude fat was the second most abundant component in the tigernut tuber. Quercetin and gallic acid were found in appreciable amounts in the tigernut oil. Although, the protein content in the tigernut milk was lower compared to the tuber, it was probably enough to impart desirable functionality to help stabilize the tigernut milk. Tigernut tuber and its derivatives can offer various options in food products. The safety of the tuber and its products can however be improved when stakeholders of the supply chain are educated and supported to implement strategies that prevent mycotoxin contamination.
PhD. Food Science
Keywords: Physicochemical; Mycotoxin Occurrence; Ghanaian Tigernuts; Cyperus Esculentus L.; functional properties